Versorgung kritisch kranker Patienten in der zentralen Notaufnahme - Michael, Mark; Kumle, Bernhard; Kümpers, Philipp; Bernhard, Michael (AINS - Anästhesiologie · Intensivmedizin · Notfallmedizin · Schmerztherapie, 2022)
Resuscitation room management of non-traumatic critically ill patients in the emergency department comprises approximately 1.5% of all emergency department visits. Critically ill patients are usually brought to the hospital by emergency medical services, where they are first examined, given initial treatment, stabilized and then transported for further in-hospital treatment. Resuscitation room management plays a key role at the interface of the out-of-hospital and in-hospital treatment chains. While the structured care of traumatological patients has been established at a very high level for decades, the care of non-traumatic critically ill patients within the framework of resuscitation room care has only come into focus in recent years and is only now being implemented in some places with professional concepts. Emergency departments at all levels of care are equipped to provide structured care for non-traumatologic shock room patients. To professionalize non-traumatic resuscitation room management, the creation of uniform standards from alerting criteria, to equipment and staffing, as well as the establishment of a uniform resuscitation room management algorithm is required. The (PRE_E-)AUD2IT-algorithm provides a structure for the non-traumatic care of critically ill patients in the resuscitation room and includes preparation, resource retrieval, handover, initial care, diagnostics, differential diagnoses and the interpretation of examination findings. This overview focuses on the management of critically ill non-traumatic patients in respect to the resuscitation room care concept.
Keywords: Notaufnahme; Betreuungskonzept; kritisch kranke Patienten; Schockraum; atraumatisch